Subjective Well-Being Pada Anggota Komunitas Laskar Sedekah Surakarta - Amalia, Yessy, Dra. Zahrotul Uyun, M. Si (2017)
Subjective well-being is an individual assessment or evaluation of the situation himself seen of life satisfaction and happiness that people felt in his life. Community members laskar sedekah Surakarta are people who dedicate their lives to helping people in need. This study used a qualitative approach, data collection method is using interviews with five research informant who is a member community of laskar sedekah Surakarta. The purpose of this study was to describe the subjective well-being owned by laskar sedekah community members. The results of this study indicate that, 1. Subjective well-being can be found on informants who are members of the community laskar sedekah Surakarta, it can be seen how feelings of happiness, touched, touched to appear in a informant when conducting social activities or action to distribute alms to the people in need, in addition to the feeling of joy, a sense of satisfaction and a sense of compassion can be distributed and perceived by the informants because alms can give directly to people in need. 2. Factors affecting the appearance of subjective well-being of informants is because of the support provided by the family and the surrounding environment. The activities carried out by informants in the community get a positive response, a form of support given to the informant in the form of motivation that builds continuously improving more activities that can provide benefits to many people, especially those who are in need. Informants also get a form of material support in order to help smooth the process of doing social activities with the community. The support received by the informants make informant became calmer, eager to undergo all the activities carried out with other community members.